Systematic review and meta-analysis of the antioxidant capacity of lycopene in the treatment of periodontal disease - López-Valverde, Nansi; López-Valverde, Antonio; Macedo de Sousa, Bruno; Blanco Rueda, José Antonio (Frontiers in Bioengineering and Biotechnology, 2024)
This systematic review with meta-analysis evaluated the antioxidant effect of lycopene as an adjuvant treatment for periodontal disease. PubMed, EMBASE and Web of Science databases were consulted. According to the PICOs strategy, inclusion criteria were established for intervention studies (RCTs) in PD subjects (participants) treated with conventional treatment and lycopene (intervention) compared to patients treated with conventional treatment (control) in which periodontal response to treatment (outcome) was assessed. The risk of bias for randomized studies was assessed using the Cochrane Risk of Bias Tool. The methodological quality of the studies included in the meta-analysis was measured using the Jadad scale. Quantitative data were analyzed using six random-effects metaanalyses, taking into account periodontal parameters: Probing Pocket Depth, Clinical Attachment Loss, Bleeding on Probing, Plaque Index, Uric Acid and Gingival Index. Six further meta-analyses were performed, according to the follow-up of the studies (short-, medium-and long-term). Of the 339 studies identified, only 7 met the eligibility criteria. The meta-analysis of the studies according to the parameters evaluated only obtained statistical significance in the assessment of PI (p=0.003). Regarding follow-up periods, PPD was significant (p=0.03) in the short term. BOP estimates were significant in the short and medium term (p=0.008 and p=0.03, respectively), IP was significant in the short and medium term (p=0.0003 and p=0.01, respectively) and GI in the short and medium term (p=0.002 and p=0.02, respectively). Heterogeneity was high (I 2 >50%) in all assessments, except for Clinical Attachment Loss (I 2 =16.7%). The results demonstrate that antioxidant treatment with lycopene could be useful as an adjunctive treatment for periodontal disease.